Association of microvascular dysfunction with clinical outcomes in patients with non-flow limiting fractional flow reserve after percutaneous coronary intervention. (August 2021) - Nishi, Takeshi; Murai, Tadashi; Waseda, Katsuhisa; Hirohata, Atsushi; Yong, Andy S.C.; Ng, Martin K.C.; Amano, Tetsuya; Barbato, Emanuele; Kakuta, Tsunekazu; Fearon, William F.
Abstract: Background: We sought to investigate prognostic implication of microvascular dysfunction as assessed by the index of microcirculatory index (IMR) in patients without residual obstructive CAD with non-flow limiting fractional flow reserve (FFR) (>0.80) following percutaneous coronary intervention (PCI). Methods: A total of 570 patients who had both post-PCI FFR and IMR values were included in the present analysis; of these, 65 patients had FFR ≤ 0.80 and 505 had FFR > 0.80. Of the 505 patients with FFR > 0.80, 137 had high IMR and 368 had low IMR. The primary outcome of the present analysis is a composite of all-cause death, spontaneous myocardial infarction, or target-vessel revascularization. Impaired microvascular function was defined as IMR ≥ 25 (high IMR). Results: During a median follow-up duration of 4.0 years, those with FFR > 0.80 and low IMR demonstrated lower rate or primary outcome event than those with FFR ≤ 0.80 (hazard ratio 0.49 [95% confidence interval 0.27–0.92], p = 0.026) and those with FFR > 0.80 and high IMR (hazard ratio 1.60 [0.99–2.16], p = 0.056). The patients with FFR > 0.80 and IMR ≥ 25 had similar rate of primary outcome event compared with those with FFR ≤ 0.80 (p = 0.49). Conclusion: Microvascular dysfunction following PCI is not rare and is associated with adverse events even in the setting of a non-flow limiting FFR; these results suggest that when performing coronary physiologic assessment following PCI, interrogating not only the epicardial vessel, but also the microvasculature is useful for the risk stratification in patients undergoing PCI.